Low vitamin K status is a potential risk factor for COVID-19 infected patients: a systematic review and meta-analysis - Liu, Wei; Liu, Xin; Kang, Shiwei; Yuan, Yadong (Frontiers in Nutrition, 2025)
ObjectiveTo provide further data support for the treatment of COVID-19 by conducting a comprehensive analysis of reports on dephosphorylated-uncarboxylated Matrix Gla Protein (dp-ucMGP), which detects the functional vitamin K status post COVID-19 infection, using meta-analysis.MethodsThis study conducted a comprehensive review and analysis of relevant research on dp-ucMGP detection in patients infected with COVID-19 through meta-analysis. The article collection period ranged from January 2024 to April 2024.ResultsA total of 6 articles were included in this study. Baseline data analysis showed that the age of patients in the COVID-19 infected group was greater than that of the non-infected control group (p = 0.030); similarly, the age of patients in the severe infection group was also greater than that of the mild infection group (p = 0.003). In the analysis of underlying diseases, statistical differences were found between the Severe group and Mild group in the presence of CVD (p = 0.010). A total of 5 studies conducted dp-ucMGP detection in both the COVID-19 infected group and the control group. The results showed that the expression of dp-ucMGP was higher in the infected group than in the control group (p < 0.001). Subgroup analysis revealed that the expression of dp-ucMGP in the severe infection group was also higher than that in the mild infection group (p < 0.001).ConclusionCOVID-19 infected patients exhibit Low Vitamin K Status, which correlates positively with the severity of infection. Supplementation of vitamin K during COVID-19 infection may potentially mitigate the progression toward severe infection, necessitating further support from clinical data.